Implementing PUSAKA for Personal and Formal Letter Writing in Junior High School - Sabrina Ayu Diningrum; Helmi Muzaki; Afiyahtun Isnaeni (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study describes the implementation of the PUSAKA (Puzzle Susun Kerangka Surat) medium in teaching personal and formal letter writing to 30 seventh-grade students in Class VII C at SMP Negeri 1 Pakisaji and examines students’ responses to its use. A qualitative descriptive design was used. Data were collected through classroom observation, documentation of student work and learning activities, and an open-ended questionnaire. The findings are limited to one Indonesian language lesson. All 30 students participated in the PUSAKA activity, while questionnaire responses were obtained from 21 students. The findings indicate that students engaged in activities such as assembling puzzles, identifying letter types, constructing outlines, and drafting complete letters, although participation levels within some groups were uneven. Of the 30 students participating in the class activity, 21 completed an open-ended questionnaire. Their responses generally described PUSAKA as an engaging and useful tool for identifying letter types, organizing ideas through outlines, and facilitating group discussions. However, some students reported unequal participation within their groups. These findings suggest that PUSAKA can serve as a context-specific instructional scaffold for letter-writing activities; however, further research is needed to evaluate its effectiveness using comparative designs and systematic writing assessments.